The formation of high-alumina clays in a pedosedimentary sequence of Marilia Formation (Western Minas Gerais, Brazil) - Coelho, C. V.S. [UNESP]; Rosolen, V. [UNESP]; Bueno, G. T.; Mesquita, A. [UNESP]; Moreira, C. A. [UNESP]; Furlan, L. M. [UNESP]; Govone, S. [UNESP] (Elsevier, 2019)
Mottled horizons and iron crusts are widespread in soil developed upslope on flat sedimentary plateau located in western of Minas Gerais State (Brazil). In the area, important deposits of high-alumina clays are located at lower topographic position suggesting a lateral transformation system from mottled horizons. External factors, generally linked to more humid climatic conditions, could explain the spatial variation of pedogenic materials in landscape. The objective of this paper is to discuss the genetic relation between the mottled and high-alumina clays horizons in a pedosedimentary sequence of Marilia Formation within the context of landscape evolution. Punctual observations using pits and auger were performed along typical soil transect. X-ray diffraction (XRD), X-ray fluorescence spectrometry (XRF), polarized light microscopy observation and scanning electron microscopy (SEM) were used to determine the affiliation between soil materials. Rietveld refinement was applied to quantify the mineralogical phases of the different layers. The results showed that both, mottled and high-alumina clays are a ferruginous depleted material, inherited from the iron crust dissolution. The horizons are aligned in the topography, despite the longer permanence of water table in depressed zones of the plateau which enhances iron dissolution and relative enrichment of gibbsite. The relative preservation of the iron crusts occurs in the altitude > 980 masl; below this level iron crusts disappear due to a generalized elevation of the groundwater in the flat plateau.
Keywords: Hydromorphy; Kaolinite-gibbsite; Marilia formation; Planation surface